Self-Regulation and Self-Care Model on Diabetic Foot Ulcer Prevention Behaviors - Fitriatul Jannah; Iswati Iswati; Hermanto Wijaya (GLOBAL HEALTH SCIENCE GROUP, 2025)
Diabetic foot ulcer (DFU) remains a major complication of type 2 diabetes mellitus (T2DM), with high recurrence and amputation rates worldwide. Effective prevention relies on self-care behaviors, which are strongly influenced by patients’ self-regulation capacity. However, many patients struggle with maintaining consistent self-care due to low levels of self-regulation. This study aimed to develop and examine a self-regulation model based on self-care theory in relation to DFU prevention behaviors among patients with T2DM. An explanatory cross-sectional design was employed with 125 purposively selected T2DM patients in Surabaya, Indonesia. Data were collected on demographic characteristics, social support, illness representation, emotional responses, symptom interpretation, coping, self-care agency (knowledge, skills, and motivation), and DFU prevention behaviors. Structural equation modeling was used to test the hypothesized relationships. The instrument used was a questionnaire, and SEM-PLS analysis was conducted. The next stage involved a Focus Group Discussion (FGD) and expert consultation for the development of the final module. Social support (T= 3,579, p = 0.000) and illness representation (T = 7,059, p = 0.000) had significant positive effects on self-care agency, while negative emotional responses reduced self-care capacity (T = 4,788, p = 0.000). Self-care agency positively influenced DFU prevention behaviors (T = 7,696, p = 0.000). Coping strategies also had a significant effect on prevention behaviors (T = 2,093, p = 0.000). Demographic factors showed no direct effect on self-care agency. The self-regulation model based on self-care theory demonstrates that psychosocial factors, particularly social support, illness representation, emotional regulation, and coping strategies, play a more crucial role than demographic characteristics in shaping DFU preventive behaviors. This study concludes that preventive behavior for diabetic foot ulcers among patients with type 2 diabetes mellitus is mainly influenced by psychosocial and behavioral factors, particularly self-care agency, illness representation, emotional responses, and social support.